KESEHATAN REPRODUKSI REMAJA : PERMASALAHAN DAN UPAYA PENCEGAHANNYA MELALUI KIE PADA REMAJA - Wahyu Nuraisya (Jurnal Inovasi, Pemberdayaan dan Pengabdian Masyarakat, 2023)
Complex problems related to reproductive health occur in adolescents ranging from pregnancy, abortion, drugs, STDs. CEI on Adolescent Reproductive Health (ARH) related to problems and prevention efforts could minimize the occurrence of ARH problems in adolescents. CEI ARH was carried out using lecture method, showing videos/pictures and questions and answers. The technique before lecture was a pre test followed by a post test. ARH material was about ARH related problems and prevention efforts. Media used power point, laptop, mic and LCD. The activity was carried out at SMPN 1 Kandangan District, Kediri Regency on February 28, conducting a location survey, March 06, 2023 coordination with the school, and March 07, 2023 implementation. The target of the activity was 40 teenagers. The level of knowledge of adolescents on the post-test results of the majority of adolescents increased by 85% to be good after being given KIE, while the results of the pre-test were 47.5%. The achievement of these goals was a successful implementation of IEC where there was an increase in knowledge about ARH. Cross-sector cooperation between school parents, and local Puskesmas was very supportive in efforts to overcome all problems and related prevention to adolescent reproductive health.